Senolysis of gemcitabine‐induced senescent human pancreatic cancer cells - Mohammad Mahbubul Hoque; Yuichi Iida; Hitoshi Kotani; Mamoru Harada (Cancer Reports, 2024)
Abstract Introduction Gemcitabine (GEM) is often used to treat pancreatic cancer. Many anti‐cancer drugs induce cancer cell death, but some cells survive after cell cycle arrest. Such a response to DNA damage is termed cellular senescence. Certain drugs, including the Bcl‐2‐family inhibitor ABT‐263, kill senescent cells; this is termed senolysis. In this study, we examined the therapeutic benefits of ABT‐263 in GEM‐induced senescence of human pancreatic cancer cells. Methods and Results Of four pancreatic cancer cell lines (PANC‐1, AsPC‐1, CFPAC‐1, and PANC10.05), GEM induced senescent features in PANC‐1 and AsPC‐1 cells, including increases in the cell sizes and expression levels of mRNAs encoding interleukin (IL)‐6/IL‐8 and induction of β‐galactosidase. Successive treatment with GEM and ABT‐263 triggered apoptosis in PANC‐1 and AsPC‐1 cells and suppressed colony formation significantly. Senolysis of GEM‐induced senescent pancreatic cancer cells by ABT‐263 was triggered by a Bcl‐xL inhibitor, but not by a Bcl‐2 inhibitor, suggesting a central role for Bcl‐xL in senolysis. In a xenograft mouse model, combined treatment with GEM and ABT‐737 (an ABT‐263 analog exhibiting the same specificity) suppressed in vivo growth of AsPC‐1 significantly. Conclusion Together, our results indicate that sequential treatment with GEM and senolytic drugs effectively kill human pancreatic cancer cells.